Effect of methacrylic acid monomer on the reverse salt diffusion in chemical grafted forward osmosis membrane - Siti Nur Atasha, Mohamad; Siti Nudra Shafinie, Ab Aziz; Mazrul Nizam, Abu Seman (The Italian Association of Chemical Engineering, 2023)
Reverse salt diffusion (RSD) is a common issue in forward osmosis (FO) membrane normally contribute to substantial fouling and lead to a lower water flux. Commercial nanofiltration (NF) membrane surface was grafted using chemical grafting for controlling this RSD issue. Different concentrations of 0.3, 0.6, and 1.0 M of methacrylic acid (MA) were selected as main monomer while potassium persulfate and sodium metabisulfite (K2S2O8/Na2S2O5) with concentration of 0.01 M as pair of initiators were used for the grafting modification. Then the grafted membrane was evaluated in term water flux (Jw) and RSD using 1 M sodium chloride (NaCl) as draw solution. The result shows that, the highest Jw (0.7534 L/m2.h) and the lowest RSD (4.272 g/m2.h) both were recorded at the grafting of 30 min with 1.0 M concentration of MA. Both performance increase with the increasing in the MA concentration and grafting time. Therefore, modification of the commercial NF membrane using chemical grafting can therefore be used as an alternative technique for enhancing the performance of commercial membrane in the application of FO.